Understanding critical success factors and perceived future among micro and small firms through entrepreneurial action theory - Duarte Alonso, Abel; Kok, Seng (Emerald Group Publishing Ltd., 2020)
Purpose – This study aims to examine how owners and managers of micro and small enterprises perceive firm success and the future of their businesses. Entrepreneurial action theory is adopted in the analysis and a modified theoretical framework is proposed.